1993
DOI: 10.1111/j.1365-2621.1993.tb04300.x
|View full text |Cite
|
Sign up to set email alerts
|

Soya Proteins Functional and Sensory Characteristics Improved in Cornminuted bleats

Abstract: Soya proteins (flour, concentrate, isolate) were incorporated in formulations of frankfurters as preemulsified fat (PEF) and as powders. Sensory analysis showed that incorporation of soya proteins as PEF resulted in a reduction of specific soybean off-flavor (beany and bitterness notes) and off-aroma. Soya proteins added as PEF increased water-holding capacity and yield, decreased cook losses, and had no detrimental effect on color. Using soya proteins as stabilizer in PEF could improve functionality of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 8 publications
1
33
0
1
Order By: Relevance
“…This result suggests an inverse relationship between Moringa inclusion levels and weight loss. A similar trend was reported by Lecomte et al, (1993) that cooking yield represents the retention of water and solutes during processing of food products. Ray et al (1981) also observed significant increase (P<0.05) in cooking yield up to 26% soy concentration in his study using ground beef.…”
Section: Source Of Raw Materialssupporting
confidence: 85%
See 1 more Smart Citation
“…This result suggests an inverse relationship between Moringa inclusion levels and weight loss. A similar trend was reported by Lecomte et al, (1993) that cooking yield represents the retention of water and solutes during processing of food products. Ray et al (1981) also observed significant increase (P<0.05) in cooking yield up to 26% soy concentration in his study using ground beef.…”
Section: Source Of Raw Materialssupporting
confidence: 85%
“…(Hossein, 2011). They are used in meat products as a binder for improving yields, as a gelling agent to enhance emulsion stability and as meat replacement to reduce cost (Lecomte et al, 1993;Rentfrow et al, 2004).The health benefits of soy in meat include prevention of heart diseases, cancer, high blood pressure, diabetesrelated disease and many others. Soy bean oil is rich in fatty acids and devoid of cholesterol.…”
Section: Introductionmentioning
confidence: 99%
“…The duration for stabilization of foam represented by foam stability was 3 h. The results are statistically significant and match with the standard pea and soybean protein isolate having water absorption capacity 1.7±0.1 and 1.3±0.1, and oil absorption capacity 9.2±0.1 and 1.1± 0.1, respectively. Further the foam stability (%) was observed 94±4 and 93±3, respectively for pea and soybean protein isolate (Lecomte et al 1993;Fernandez-Quintela et al 1997). Thus the water and oil absorption capacity and foaming properties of apricot protein isolate were fairly good and can be used to fortify soft drinks and beverages to prepare protein enriched ready to serve drinks.…”
Section: Composition and Functional Properties Of Protein Isolatementioning
confidence: 90%
“…Soy proteins being an cheap source of food protein have been used extensively in meat products as a binder for improving yields, as a gelling agent to enhance emulsion stability and as a meat replacement to reduce costs (Lecomte et al 1993; Rentfrow et al 2004). …”
Section: Introductionmentioning
confidence: 99%